PARTISIPASI MASYARAKAT DALAM PENGELOLAAN WISATA PANTAI DEPOK DI DESA KRETEK PARANGTRITIS - Nawawi, Ahmad (JURNAL NASIONAL PARIWISATA, 2013)
The main focus of this research is to assess the level of participation and community involvement in the management of Depok beach in the village of Kretek Parangtritis, Bantul. Data analysis was performed with the understanding and assemble the data that has been collected systematically. The goal is to prove the public response to the tourism and the level of community participation in protecting the coastal environment Depok see the reasons already given.The results of the analysis and interpretation of data mentioned that the management of coastal tourism Depok administratively still united by a lokal government district of Bantul with other tourist areas in the village Parangtritis. Community participation in tourism management Depok Beach Travel proved by establishing cooperative Mina Bahari 45 Depok Beach. Recommendations of this study is to increase community participation in coastal resorts Depok through the arrangement and layout arrangements trade stalls and attractions managers